Hippocampal and striatal volumes correlate with spatial memory impairment in Huntington's disease. Issue 11 (13th September 2021) - Glikmann‐Johnston, Yifat; Mercieca, Emily‐Clare; Carmichael, Anna M.; Alexander, Bonnie; Harding, Ian H.; Stout, Julie C.
Abstract: Spatial memory impairments are observed in people with Huntington's disease (HD), however, the domain of spatial memory has received little focus when characterizing the cognitive phenotype of HD. Spatial memory is traditionally thought to be a hippocampal‐dependent function, while the neuropathology of HD centers on the striatum. Alongside spatial memory deficits in HD, recent neurocognitive theories suggest that a larger brain network is involved, including the striatum. We examined the relationship between hippocampal and striatal volumes and spatial memory in 36 HD gene expansion carriers, including premanifest ( n = 24) and early manifest HD ( n = 12), and 32 matched healthy controls. We assessed spatial memory with Paired Associates Learning, Rey–Osterrieth Complex Figure Test, and the Virtual House task, which assesses three components of spatial memory: navigation, object location, and plan drawing. Caudate nucleus, putamen, and hippocampal volumes were manually segmented on T1‐weighted MR images. As expected, caudate nucleus and putamen volumes were significantly smaller in the HD group compared to controls, with manifest HD having more severe atrophy than the premanifest HD group. Hippocampal volumes did not differ significantly between HD and control groups. Nonetheless, on average, the HD group performed significantly worse than controls across all spatial memory tasks. The spatial memory components of object location and recall of figural and topographical drawings were associated with striatal and hippocampal volumes in the HD cohort. We provide a case to include spatial memory impairments in the cognitive phenotype of HD, and extend the neurocognitive picture of HD beyond its primary pathology within the striatum. Abstract : Spatial memory impairments in people with Huntington's disease (HD) were related to volumes of the caudate nucleus, putamen, and hippocampus. We suggest that spatial memory impairments should be included in the cognitive phenotype of HD.